EFL Students’ Functional and Cognitive Dependency on ChatGPT in EFL Academic Writing - Awalia Putri, Fitri; Suratman, Suratman; Annisah, Annisah; Waliyudin, Waliyudin (Universitas Jambi, Magister Program of English Education Department, 2026)
The increasing use of ChatGPT in academic writing has raised concerns about students' dependency on artificial intelligence, particularly in EFL contexts. This study examines students' functional and cognitive dependency on ChatGPT as theoretically distinct constructs and describes dependency patterns across gender. A descriptive quantitative design was employed involving ten fourth-semester English Education students at STKIP Taman Siswa Bima. Data were collected through a questionnaire (functional: α = .830; cognitive: α = .632) and self-reflection responses analysed thematically, with findings triangulated to strengthen credibility. The results revealed higher functional dependency (M = 3.66) than cognitive dependency (M = 3.29). Students primarily relied on ChatGPT for grammar correction, vocabulary improvement, sentence construction, and paraphrasing, while cognitive support was associated with idea generation and argument development. Thematic analysis yielded three themes: reasons for use, perceived benefits, and awareness of over-reliance. Gender differences were minimal. The novelty of this study lies in demonstrating that AI dependency operates across qualitatively different levels of the writing process, extending AI-assisted writing frameworks and contributing to learner autonomy discourse by suggesting that EFL learners can exercise selective AI use as a form of strategic autonomy.